Degradation of iopamidol by three UV-based oxidation processes: Kinetics, pathways, and formation of iodinated disinfection byproducts. (April 2019) - Zhao, Xi; Jiang, Jin; Pang, Suyan; Guan, Chaoting; Li, Juan; Wang, Zhen; Ma, Jun; Luo, Congwei
Abstract: In this study, the degradation kinetics of iopamidol (IPM) by three different UV-based oxidation processes including UV/hydrogen peroxide (H2 O2 ), UV/persulfate (PDS) and UV/chlorine (NaClO) were examined and the potential formation of iodinated disinfection byproducts (I-DBPs) in these processes followed by sequential chlorination was comparatively investigated. Increasing pH led to the decrease of IPM degradation rate in UV/NaClO, while it showed negligible impact in UV/PDS and UV/H2 O2 . Common background constituents such as chloride ions (Cl − ), carbonate (HCO3 − ) and natural organic matter (NOM) inhibited IPM degradation in UV/H2 O2 and UV/PDS, while IPM degradation in UV/NaClO was only suppressed by NOM but not Cl − and HCO3 − . The differences in transformation products of IPM treated by hydroxyl radical (HO*), sulfate radical (SO4 * - ), as well as Cl2 * - and ClO* generated in these processes, respectively, were also analyzed. The results suggested that hydroxyl radical (HO*) preferred to form hydroxylated derivatives. Sulfate radical (SO4*-) preferred to oxidize amino group of IPM to nitro group, while Cl2 * - and ClO* favored the generation of chlorine-containing products. Moreover, specific I-DBPs (i.e., iodoform (IF) and monoiodacetic acid (MIAA)) were detected in the three processes followed by chlorination. The addition of NOM had little effect on IF formation of three processes, while MIAA formation decreased in all processes except UV/H2 O2 . Given that the formation of I-DBPs in UV/NaClO was less than those formed in the other two processes, UV/NaClO seems to be a more promising strategy for effectively removing IPM with alleviation of I-DBPs in treated water effluents. Graphical abstract: Image 1 Highlights: Degradation of IPM by H2 O2, PDS and NaClO under UV irradiation was examined. Kinetics modeling was performed based on reaction rates of radicals with IPM. Oxidation products of IPM by different reactive radicals were identified. Formation potential of I-DBPs in three UV-based oxidation processes was compared.